SMOC2 gene interacts with APOL1 in the development of end-stage kidney disease: A genome-wide association study - Chaudhary, Ninad S.; Armstrong, Nicole D.; Hidalgo, Bertha A.; Gutiérrez, Orlando M.; Hellwege, Jacklyn N.; Limdi, Nita A.; Reynolds, Richard J.; Judd, Suzanne E.; Nadkarni, Girish N.; Lange, Leslie; Winkler, Cheryl A.; Kopp, Jeffrey B.; et al. (Frontiers in Medicine, 2022)
Background Some but not all African-Americans (AA) who carry APOL1 nephropathy risk variants (APOL1) develop kidney failure (end-stage kidney disease, ESKD). To identify genetic modifiers, we assessed gene–gene interactions in a large prospective cohort of the REasons for Geographic and Racial Differences in Stroke (REGARDS) study. Methods Genotypes from 8,074 AA participants were obtained from Illumina Infinium Multi-Ethnic AMR/AFR Extended BeadChip. We compared 388 incident ESKD cases with 7,686 non-ESKD controls, using a two-locus interaction approach. Logistic regression was used to examine the effect of APOL1 risk status (using recessive and additive models), single nucleotide polymorphism (SNP), and APOL1*SNP interaction on incident ESKD, adjusting for age, sex, and ancestry. APOL1*SNP interactions that met the threshold of 1.0 × 10−5 were replicated in the Genetics of Hypertension Associated Treatment (GenHAT) study (626 ESKD cases and 6,165 controls). In a sensitivity analysis, models were additionally adjusted for diabetes status. We conducted additional replication in the BioVU study. Results Two APOL1 risk alleles prevalence (recessive model) was similar in the REGARDS and GenHAT studies. Only one APOL1–SNP interaction, for rs7067944 on chromosome 10, ~10 KB from the PCAT5 gene met the genome-wide statistical threshold (Pinteraction = 3.4 × 10−8), but this interaction was not replicated in the GenHAT study. Among other relevant top findings (with Pinteraction < 1.0 × 10−5), a variant (rs2181251) near SMOC2 on chromosome six interacted with APOL1 risk status (additive) on ESKD outcomes (REGARDS study, Pinteraction =5.3 × 10−6) but the association was not replicated (GenHAT study, Pinteraction = 0.07, BioVU study, Pinteraction = 0.53). The association with the locus near SMOC2 persisted further in stratified analyses. Among those who inherited ≥1 alternate allele of rs2181251, APOL1 was associated with an increased risk of incident ESKD (OR [95%CI] = 2.27[1.53, 3.37]) but APOL1 was not associated with ESKD in the absence of the alternate allele (OR [95%CI] = 1.34[0.96, 1.85]) in the REGARDS study. The associations were consistent after adjusting for diabetes. Conclusion In a large genome-wide association study of AAs, a locus SMOC2 exhibited a significant interaction with the APOL1 locus. SMOC2 contributes to the progression of fibrosis after kidney injury and the interaction with APOL1 variants may contribute to an explanation for why only some APOLI high-risk individuals develop ESKD.